Estudio económico de la producción y comercialización de hortalizas orgánicas y convencionales en la ciudad de Calceta. - Macías Loor, Diana Elizabeth (2011)
The existing research was carried out in the city of stocking, presented the economic survey of the production and marketing of organic and conventional produce in the city of stocking whose purpose was to determine it this agricultural activity contributes or not to the economic development of producers as thememanaging to diagnose the approximate number of these producers of vegetables; quienes provided information that helped carry out the analysis of the profitability and the cost of production of the same. Thus through a market survey was the analysis of the demand for the consumption of conventional and organic vegetables in the city of sock. I was finally carried out a comparative analysis between the production and marketing of conventional vegetables and organic vegetables in the city of sock. To develop this work, applied field research and bibliographic research, used the technique of observation and applied surveys both producers and consumers of vegetables, which allowed to know the reality of many of our producersthose who need greater support govemmental or private actors, since there are a myriad of problems at the time of the production and marketing which affects them in the performance. With regard to citizenship, a large percentage do not consume organic products, mainly due to the low offer on the market and thus its high prices, but want to do it clean would consume them.